2020
DOI: 10.1111/cge.13812
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic variants in PPP1R13L cause paediatric dilated cardiomyopathy

Abstract: Childhood dilated cardiomyopathy (DCM) is a leading cause of heart failure requiring cardiac transplantation and approximately 5% of cases result in sudden death. Knowledge of the underlying genetic cause can aid prognostication and clinical management and enables accurate recurrence risk counselling for the family. Here we used genomic sequencing to identify the causative genetic variant(s) in families with children affected by severe DCM. In an international collaborative effort facilitated by GeneMatcher, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…With the aid of this tool, we identified a novel PPP1R13L stop-gain variant (c.580C > T: p.Gln194Ter) in an autosomal recessive ACM pedigree. In recent years, PPP1R13L variants have been identified in patients with cardio-cutaneous syndrome [ 15 , 20 ], cattle woolly haircoat syndrome [ 14 ], DCM [ 20 ], and ACM [ 13 ] (Table 1 ). The location of all reported variants was shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With the aid of this tool, we identified a novel PPP1R13L stop-gain variant (c.580C > T: p.Gln194Ter) in an autosomal recessive ACM pedigree. In recent years, PPP1R13L variants have been identified in patients with cardio-cutaneous syndrome [ 15 , 20 ], cattle woolly haircoat syndrome [ 14 ], DCM [ 20 ], and ACM [ 13 ] (Table 1 ). The location of all reported variants was shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Few WGS cardiomyopathy studies were found in the literature, presumably due to cost and the current bioinformatic burden relating to data storage and analysis. Two novel cardiomyopathy genes, MYBPHL and PPP1R13L , have been identified through WGS in familial DCM,34 35 but pathogenic variation in these genes has not been described in cardiomyopathy since their original report.…”
Section: Wgs In Cardiomyopathymentioning
confidence: 99%
“…Affected individuals develop severe dilated cardiomyopathy (DCM) leading to death or cardiac transplant in childhood, and cutaneous manifestations including wooly or wiry hair, wedged teeth, xerotic skin, dystrophic nails, cleft palate, and corneal abnormalities. 1,2…”
mentioning
confidence: 99%
“…4 Loss of function is the underlying mechanism of mutations in this gene, with the majority of reported disease-causing variants being truncating (nonsense, frameshift, and splicing variants). 1 Both parents are heterozygous for the variant, which contains a duplica- iASPP regulates desmosomes, which are proteins that anchor together cells subject to physical stress such as skin and myocytes. 1 Other cardiocutaneous conditions (such as Naxos and Carvajal syndromes) share similar desmosomal defects and present with structurally abnormal, arrhythmogenic myocardium and cutaneous features resembling ectodermal dysplasia.…”
mentioning
confidence: 99%
See 1 more Smart Citation